Hypocretin and brain β-amyloid peptide interactions in cognitive disorders and narcolepsy - Dauvilliers, Yves A.; Lehmann, Sylvain; Jaussent, Isabelle; Gabelle, Audrey (Frontiers in Aging Neuroscience, 2014)
Objective: To examine relationships between cerebrospinal fluid (CSF) Alzheimer’ disease (AD) biomarkers and hypocretin-1 levels in patients with cognitive abnormalities and hypocretin-deficient narcolepsy-cataplexy (NC), estimate diagnostic accuracy, and determine correlations with sleep disturbances. Background: Sleep disturbances are frequent in AD. Interactions between brain β-amyloid (Aβ) aggregation and a wake-related neurotransmitter hypocretin have been reported in a mouse model of AD. Methods: Ninety-one cognitive patients (37 AD, 16 mild cognitive impairment – MCI that converts to AD, 38 other dementias) and 15 elderly patients with NC were recruited. Patients were diagnosed blind to CSF results. CSF A42, total tau, ptau181, and hypocretin-1 were measured. Sleep disturbances were assessed with questionnaires in 32 cognitive patients. Results: Lower CSF Aβ42 but higher tau and P-tau levels were found in AD and MCI compared to other dementias. CSF hypocretin-1 levels were higher in patients with MCI due to AD compared to other dementias, with a similar tendency for patients with advanced AD. CSF hypocretin-1 was significantly and independently associated with AD/MCI due to AD, with an OR of 2.70 after full adjustment, exceeding that for Aβ42. Aβ42 correlated positively with hypocretin-1 levels in advanced stage AD. No association was found between sleep disturbances and CSF biomarkers. No patients with NC achieved pathological cutoffs for Aβ42, with respectively one and four patients with NC above tau and P-tau cutoffs and no correlations between hypocretin-1 and other biomarkers. Conclusions: Our results suggest a pathophysiological relationship between Aβ42 and hypocretin-1 in the AD process, with higher CSF hypocretin-1 levels in early disease stages. Further longitudinal studies are needed to validate these biomarker interactions and to determine the cause-effect relationship and the role of wake/sleep behavior in amyloid plaque regulation